(untitled) (Eureka Journal of Physical and Chemical Research, 2025)
An experimental diabetes model was modeled using alloxan. Once the model was satisfied, it was treated using As-GAM and Shifo natural biologically active food supplement (NBAFS). Effects on blood lipid spectrum, glucose, AlT, AsT, and total protein indicators were studied and compared in diabetic rats and treated groups. Positive indicators were achieved in the groups given Shifo and As-GAM NBAFSs prepared from plants growing in the territory of Uzbekistan.